2018
DOI: 10.1002/lpor.201800109
|View full text |Cite
|
Sign up to set email alerts
|

Chirality of Symmetric Resonant Heterostructures

Abstract: Chiroptical effects arising in mirror‐symmetric geometrically achiral resonant heterostructures are investigated. It is shown that coalescence of extrinsic chirality, heterogeneous morphology, and substrate‐induced break of symmetry leads to pronounced circular dichroism and circular birefringence. The physics of the involved phenomena is elucidated by studying spin‐splitting in scattering and hybridized dipolar modes of a heterodimer made of gold and silicon nanoparticles of the same shape and size. The work … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 76 publications
(199 reference statements)
0
15
0
Order By: Relevance
“…The resulting geometry differs from planar asymmetric crescent structures, which show a dependence of the chiroptical response on the illumination direction . Planar chiral structures in general may exhibit true chirality only due to the substrate induced symmetry breaking or fabrication imperfections . Residuals of the templating polymer spheres, visible in the centre of the crescent (Figure b), do not affect significantly the optical properties and may be removed by immersion in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting geometry differs from planar asymmetric crescent structures, which show a dependence of the chiroptical response on the illumination direction . Planar chiral structures in general may exhibit true chirality only due to the substrate induced symmetry breaking or fabrication imperfections . Residuals of the templating polymer spheres, visible in the centre of the crescent (Figure b), do not affect significantly the optical properties and may be removed by immersion in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…[56] Planar chiral structures in general may exhibit true chirality only due to the substrate induced symmetry breaking or fabrication imperfections. [1,3,45,57,58] Residuals of the templating polymer spheres, visible in the centre of the crescent (Figure 2b), do not affect significantly the optical properties and may be removed by immersion in organic solvents. www.advopticalmat.de Figure 2d demonstrates the high regularity of the chiral single crescent array that is inherited from the colloidal mask.…”
Section: Realization Of Individual 3d Chiral Crescentsmentioning
confidence: 99%
“…In contrast, truly chiral objects retain their chiroptical response upon flipping the substrate and exhibit chiral responses in a homogenous refractive index (RI) environment. [33,37,52,53,58] Similarly, we can observe that mirror-symmetric objects can resemble (truly) chiral objects if their angle of illumination is oblique, i.e., if the substrate is tilted (Figure 1c, right). This phenomenon is known as extrinsic chirality.…”
Section: What Is Chirality In the Context Of Chiral Optics And Why Does It Mattermentioning
confidence: 76%
“…To date, several studies [ 5,21–29 ] have confirmed the potential of high refractive index dielectric nanostructures to enhance optical chirality in the near field. The performance of a silicon sphere in optical chirality enhancement was analyzed based on the Mie theory, and it was found that the optical chirality enhancement was always accompanied with magnetic resonances and increased for higher resonance orders.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Subsequently, studies on the optical chirality properties of nanosphere homo‐ and heterodimers demonstrated that the optical chirality of dielectric dimers was superior to that of metal dimers. [ 21,24–27 ] In addition, metasurfaces composed of high refractive index disks can be structurally designed to achieve large‐volume uniform‐sign optical chirality enhancement by simultaneously manipulating the electric and magnetic resonances, and particularly achieve the best performance at the Kerker condition. [ 5,21,28 ] At the bud of this new trend, it is worth looking into the effects of various modes and multipolar interference in Mie resonators on optical chirality.…”
Section: Introductionmentioning
confidence: 99%